Fusion genes with ALK as recurrent partner in ependymoma-like gliomas: a new brain tumor entity?. Issue 10 (19th March 2015) - Olsen, Thale Kristin; Panagopoulos, Ioannis; Meling, Torstein R.; Micci, Francesca; Gorunova, Ludmila; Thorsen, Jim; Due-Tønnessen, Bernt; Scheie, David; Lund-Iversen, Marius; Krossnes, Bård; Saxhaug, Cathrine; Heim, Sverre; et al.
Abstract: Background: We have previously characterized 19 ependymal tumors using Giemsa banding and high-resolution comparative genomic hybridization. The aim of this study was to analyze these tumors searching for fusion genes. Methods: RNA sequencing was performed in 12 samples. Potential fusion transcripts were assessed by seed count and structural chromosomal aberrations. Transcripts of interest were validated using fluorescence in situ hybridization and PCR followed by direct sequencing. Results: RNA sequencing identified rearrangements of the anaplastic lymphoma kinase gene ( ALK ) in 2 samples. Both tumors harbored structural aberrations involving the ALK locus 2p23. Tumor 1 had an unbalanced t(2;14)(p23;q22) translocation which led to the fusion gene KTN1-ALK . Tumor 2 had an interstitial del(2)(p16p23) deletion causing the fusion of CCDC88A and ALK . In both samples, the breakpoint of ALK was located between exons 19 and 20. Both patients were infants and both tumors were supratentorial. The tumors were well demarcated from surrounding tissue and had both ependymal and astrocytic features but were diagnosed and treated as ependymomas. Conclusions: By combining karyotyping and RNA sequencing, we identified the 2 first ever reported ALK rearrangements in CNS tumors. Such rearrangements may represent the hallmark of a new entity of pediatric glioma characterized by both ependymal and astrocytic features. Our findings are of particular importance because crizotinib, a selective ALK inhibitor, has demonstrated effect in patients with lung cancer harboring ALK rearrangements. Thus, ALK emerges as an interesting therapeutic target in patients with ependymal tumors carrying ALK fusions.